TRANSFORMASI AKUNTANSI KEUANGAN MELALUI BLOCKCHAIN: MENJAMIN KEANDALAN DAN TRANSPARANSI DI ERA DIGITAL - Arsal, Muryani; Saleh, Nurfadilah; Lestari , Nurwinda; Paramitha , Adhelia (Cattleya Darmaya Fortuna, 2025)
The integration of blockchain technology in financial accounting has significantly contributed to enhancing transparency, reliability, and operational efficiency. This research aims to explore the role of blockchain in financial reporting, focusing on its impact on data integrity and stakeholder trust. The study employs a comprehensive literature review method, analyzing relevant sources to identify key themes and insights. Results indicate that blockchain enables immutable and decentralized transaction records, reducing manipulation risks and facilitating efficient audit processes. Despite its potential, the adoption of blockchain in Indonesia faces challenges, including infrastructure readiness and limited understanding of the technology. This study underscores the importance of blockchain in modern financial practices and its relevance to Indonesia's accounting landscape.